Cultivating partnerships to incorporate health promotion modules into primary school curricula: a case study in France - Johnson, Stacey; Laham, Sandy; Blanc, Samantha; Bellanger, Martine (Frontiers in Education, 2024)
School-based health promotion (HP) emerged from the settings-based approach. Children from disadvantaged neighborhoods benefit from HP in their school. Teachers deliver HP modules but need additional resources. This case study aimed to form a transdisciplinary partnership in a socially disadvantaged area to co-develop and embed HP modules into existing curricula. A 3-stage framework was used in this study. Stage 1 cultivated partnerships, reviewed evidence and existing data. Stage 2 generated ideas and co-developed HP modules. Stage 3 trialed the modules within primary school classrooms. Stage 1 resulted in a partnership between city authorities, a primary school and a comprehensive cancer center all located in the same community in France. The reviewed data and evidence provided 18 examples of school-based HP programs and showed that the school is in a highly disadvantaged neighborhood with a large immigrant population. Stage 2 developed 3 HP modules: “Taste and Science Week,” “Nutrition Weeks,” and “Breakfast Week,” each embedded as add-ins into existing math and science lessons and workshops. Finally, stage 3 trialed the modules in 10 first to fifth grade classrooms impacting 214 total students. Transdisciplinary partnerships help co-create and support evidence-driven HP programs. This collaborative approach enabled primary school teachers to effectively embed the HP modules into pre-existing math and science curricula. Families and volunteers are an integral part of successful HP programs however, limited participation was a challenge. Further research is needed to evaluate indicators such as student academic success and health behavior change.